Lack of connexin43-mediated Bergmann glial gap junctional coupling does not affect cerebellar long-term depression, motor coordination, or eyeblink conditioning - Tanaka, Mika; Yamaguchi, Kazuhiko; Tatsukawa, Tetsuya; Nishioka, Chieko; Nishiyama, Hiroshi; Theis, Martin; Willecke, Klaus; Itohara, Shigeyoshi (Frontiers in Behavioral Neuroscience, 2008)
Bergmann glial cells are specialized astrocytes in the cerebellum. In the mature cerebellar molecular layer, Bergmann glial processes are closely associated with Purkinje cells, enclosing Purkinje cell dendritic synapses with a glial sheath. There is intensive gap junctional coupling between Bergmann glial processes, but their significance in cerebellar functions is not known. Connexin43 (Cx43), a major component of astrocytic gap junction channels, is abundantly expressed in Bergmann glial cells. To examine the role of Cx43-mediated gap junctions between Bergmann glial cells in cerebellar functions, we generated Cx43 conditional knockout mice with the S100b-Cre transgenic line (Cx43fl/fl:S100b-Cre), which exhibited a significant loss of Cx43 in the Bergmann glial cells and astrocytes in the cerebellum with a postnatal onset. The Cx43fl/fl:S100b-Cre mice had normal cerebellar architecture. Although gap junctional coupling between the Bergmann glial cells measured by spreading of microinjected Lucifer yellow was virtually abolished in Cx43fl/fl:S100b-Cre mice, electrophysiologic analysis revealed that cerebellar long-term depression could be induced and maintained normally in thier cerebellar slices. In addition, at the behavioral level, Cx43fl/fl:S100b-Cre mice had normal motor coordination in the rotarod task and normal conditioned eyelid response. Our findings suggest that Cx43-mediated gap junctional coupling between Bergmann glial cells is not necessary for the neuron-glia interactions required for cerebellum-dependent motor coordination and motor learning.